Performance Indicators Labor in the Sector of Tourism (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the labor productivity of tourism workers,labor productivity in valuation, labor productivity in physical terms, a comprehensive indicator of the dynamics of labor efficiency, measured by the ratio of revenue from the sale of a tourism product to the average number of employees for the corresponding period.